2020
DOI: 10.47892/rgp.2020.404.1172
|View full text |Cite
|
Sign up to set email alerts
|

Proctitis infecciosa transmitida sexualmente: reto diagnóstico y recomendaciones de tratamiento

Abstract: La proctitis infecciosa (PI) transmitida sexualmente es un proceso inflamatorio del recto secundario a la infección por gérmenes de transmisión sexual. Neisseria gonorrhoeae, Chlamydia trachomatis, Treponema pallidum y el virus herpes simple (VHS) son las causas más comunes. Es más prevalente en hombres que tienen sexo con hombres (HSH) y en pacientes con infección por el virus de inmunodeficiencia humana (VIH), sin embargo, también se diagnostica en heterosexuales por cambios en el comportamiento sexual. La u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…These findings are in agreement with previous studies, only age is slightly lower compared to other publications, which reported an average of approximately 43 years [9,10]. These young patients typically present anal pain, tenesmus, constipation, and rectal bleeding [11]. In our study it was not possible to estimate the prevalence of these symptoms due to the lack of systematized information in the medical records, a problem that is quite common in our country.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are in agreement with previous studies, only age is slightly lower compared to other publications, which reported an average of approximately 43 years [9,10]. These young patients typically present anal pain, tenesmus, constipation, and rectal bleeding [11]. In our study it was not possible to estimate the prevalence of these symptoms due to the lack of systematized information in the medical records, a problem that is quite common in our country.…”
Section: Discussionsupporting
confidence: 88%
“…In this case, according to the clinical findings, the infectious agents ( Neisseria gonorrhoeae and MPXV) could have caused IP. However, the most common cause of IP is Neisseria gonorrhoeae, and its signs and symptoms were reported in this case; in addition, the response to treatment with ceftriaxone was good, which suggests that this microorganism may have been responsible; excluding Treponema Pallidum (primary syphilis), whose incubation period is usually from two to six weeks 16 .…”
Section: Discussionmentioning
confidence: 55%
“…Currently, there is no specific or approved treatment for mpox, so therapy mainly aims at managing symptoms. However, some antivirals called “of compassionate use” have been approved by the Food and Drug Administration (FDA) for treatment of human smallpox and have shown efficacy against mpox; the Centers for Disease Control and Prevention (CDC) guidelines suggest tecovirimat as first-line drug in patients with severe disease or who are at high risk of developing severe disease 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with symptoms of acute proctitis with painful perianal or mucosal ulcers detected on proctological examination should receive presumptive treatment for genital herpes [ 7 ]. The diagnosis of anorectal HSV infection can be performed using PCR, which has a higher sensitivity compared to the gold standard test (culture virus in rectal tissue) [ 19 ]. Treatment options are acyclovir 400 mg t.i.d., valganciclovir 500 mg b.i.d., or famciclovir 250 mg t.i.d., for 5-10 days [ 8 , 20 ].…”
Section: Managementmentioning
confidence: 99%